Pengaruh Tingkat Margin Murabahah dan Financing ToDeposit Ratio Terhadap NonPerforming Financing Pada Bank Umum Syariah Periode 2021 – 2024 - Fa’ikhotul Hikmah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the effect of murabahah margin levels and the Financing to Deposit Ratio (FDR) on NonPerforming Financing (NPF) in Islamic Commercial Banks in Indonesia during the period 2021 to 2024. The study employs a quantitative approach with an explanatory research design. The data used are secondary data obtained from Islamic Banking Statistics and bank financial reports. The analytical method applied is multiple linear regression. The results indicate that murabahah margin levels and FDR show an increasing trend during the observation period, while NPF fluctuates. An increase in murabahah margins may affect customers’ repayment capacity, thereby influencing the risk of nonperforming financing. On the other hand, an increase in FDR reflects higher financing distribution, but also raises potential risks if not supported by proper risk management. The findings reveal that murabahah margin levels and FDR have a significant effect on NPF, both partially and simultaneously. These results suggest that margin setting policies and financing distribution strategies play an important role in maintaining financing quality and the stability of Islamic banking. This study is expected to provide insights for Islamic banks in managing financing and risk more effectively